Functionally connected brain regions in the network activated during capsaicin inhalation. Issue 11 (23rd May 2014) - Farrell, Michael J.; Koch, Saskia; Ando, Ayaka; Cole, Leonie J.; Egan, Gary F.; Mazzone, Stuart B.
Abstract Coughing and the urge‐to‐cough are important mechanisms that protect the patency of the airways, and are coordinated by the brain. Inhaling a noxious substance leads to a widely distributed network of responses in the brain that are likely to reflect multiple functional processes requisite for perceiving, appraising, and behaviorally responding to airway challenge. The broader brain network responding to airway challenge likely contains subnetworks that are involved in the component functions required for coordinated protective behaviors. Functional connectivity analyses were used to determine whether brain responses to airway challenge could be differentiated regionally during inhalation of the tussive substance capsaicin. Seed regions were defined according to outcomes of previous activation studies that identified regional brain responses consistent with cough suppression, stimulus intensity coding, and perception of urge‐to‐cough. The subnetworks during continuous inhalation of capsaicin recapitulated the distributed regions previously implicated in discrete functional components of airway challenge. The outcomes of this study highlight the central representation of airways defence as a distributed network. Hum Brain Mapp 35:5341–5355, 2014. © 2014 Wiley Periodicals, Inc.